2003
DOI: 10.1021/jo030001k
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling of the Porphyrin-Linked Acyclic Penta- and Heptapeptides in Aqueous Trifluoroethanol

Abstract: The conjugates of porphyrin with links to the acyclic penta- and heptapeptides were synthesized to mimic natural multiple porphyrin systems. The linear penta- and heptapeptide with hydrophilic/hydrophobic alternative sequences took a random structure in aqueous trifluoroethanol (TFE). However, these polypeptides took a beta-sheet structure in the same solvent when the N-terminal Cys linked to the porphyrin, suggesting that the conjugates self-assembled via the intermolecular hydrophobic interaction between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 82 publications
1
31
0
Order By: Relevance
“…The first study of a peptide-porphyrin supramolecular self-assembly was reported in 2001 by Arai et al, who showed that conjugates 24a,b and 25 can adopt β-sheet assemblies in aqueous trifluoroethanol [74]. A follow-up study indicated that this behavior is promoted by the hydrophobic effect between neighboring porphyrins, as, under the same conditions, the free peptides are too short to fold in a β-sheet [75]. The peculiar CD and UV/Vis spectra of conjugate 24a suggest complex interactions between tetrapyrrole rings that stabilize the architecture.…”
Section: Medium and Long Peptidesmentioning
confidence: 99%
“…The first study of a peptide-porphyrin supramolecular self-assembly was reported in 2001 by Arai et al, who showed that conjugates 24a,b and 25 can adopt β-sheet assemblies in aqueous trifluoroethanol [74]. A follow-up study indicated that this behavior is promoted by the hydrophobic effect between neighboring porphyrins, as, under the same conditions, the free peptides are too short to fold in a β-sheet [75]. The peculiar CD and UV/Vis spectra of conjugate 24a suggest complex interactions between tetrapyrrole rings that stabilize the architecture.…”
Section: Medium and Long Peptidesmentioning
confidence: 99%
“…(E) Synthetic scheme for the preparation of peptideporphyrin conjugate using the bromoacetamide-cysteine reaction. (Arai et al, 2003). PpIX-Y113WF conjugate.…”
Section: Thiol-maleimide Ligationmentioning
confidence: 99%
“…A complementary reaction that can be used to link porphyrinoids to cysteine residues of peptides is the thiol-haloacetamide ligation. In particular, bromo- and iodo-acetamides have been used as electrophilic sites ( Chaloin et al, 2001 ; Arai et al, 2003 ) with the thiol serving as a nucleophile. Since the thiol on cysteine is more nucleophilic than hydroxyl and amino side-chains on other amino acids, this reaction is selective for cysteine ligation ( Giuntini et al, 2011 ).…”
Section: Porphyrin-peptide Conjugatesmentioning
confidence: 99%
See 2 more Smart Citations